Dislocation structure of tungsten irradiated by medium to high-mass ions. (1st September 2022) - Wielunska, B.; Płociński, T.; Schwarz-Selinger, T.; Mayer, M.; Jacob, W.; Ciupiński, L.
Abstract: Single crystalline tungsten was irradiated by the medium-mass ion Si with 7.5 MeV and high mass-ion W with 20.3 MeV up to a calculated peak damage level of 0.04 dpa and 0.5 dpa. The obtained dislocation structure of the damage zone was investigated by transmission electron microscopy and systematically compared with each other. Bright-field kinematical images were taken under four different two-beam diffraction conditions g = −200, 020, −110, 110 close to the [100] zone axis. The observed damage depth and damage peak position is in good agreement with the SRIM calculated damage depth profiles. The dislocation structures were investigated at the region of the damage peak because there the damage levels are comparable. In both irradiations (Si and W), the dislocation structures were similar. At the low damage level of 0.04 dpa dislocation loops and dislocation-loop clusters were found. The size of the dislocation loops in the W-irradiated tungsten sample was up to 20% higher than for the Si-irradiated sample. At the high damage level of 0.5 dpa a dislocation network consisting of dislocation-loop chains and dislocation lines was found for both irradiations. The dislocation line density was about 12% higher for the W-irradiated sample. Through comparison of the damage zone to SRIM damage depth profiles it was found that the transition from dislocation loops and dislocation-loop clusters to an ordered dislocation network takes place at about 0.08–0.1 dpa. Despite the large differences in ion mass and irradiation energy the dislocation structures were very similar.